The effect of employee ethics, trust, and service quality to customer satisfaction: a study on Malaysian telecommunications - Othman, Manisah; Kamarohim, Nor Azlina (Universal Publishers, 2022)
Purpose: The purpose of this study is to expand our knowledge by examining the effects of employees’ ethic, trust and service quality dimensions on customer satisfaction in telecommunication industry; and to identify the most important factors effects of Customer Satisfaction, if any. Design/methodology/approach: Descriptive analysis were used in this study. 413 samples were taken from the data gathered from Telecommunication’s customer in Selangor, Malaysia and we distributed online survey (263 responses) to random customer through any social media platform (WhatsApp, Facebook, Instagram, and others), and distributed hardcopy using a convenient sample to 150 customers for any telecommunications service provider. Findings: This study found out that the dimensions of service quality and customer trust which the company must focus to provide better service for customer satisfaction. This study also found that salesperson ethical treatment is not significantly affect customer satisfaction in telecommunication industry. Research limitations/implications: The main limitation of the study is that it was confined to the Selangor area only. so, the findings of Selangor cannot be generalized for the entire nation. Secondly, present study focuses only on Telecommunications Service Industry. Secondly, present study focuses only on Telecommunications Service Industry. Practical implications: The research results provide the telecommunications service provider with some knowledge and feedback in the development of management strategies to increase customer satisfaction. Telecommunications service providers must emphasize the importance of customer trust and service quality in their strategic business planning to increase customer satisfaction. Originality/value: This study contributes to the factors affect the customer satisfaction literature by proposing future research avenues.